On the contribution of Angola to the initial spread of HIV-1 (2016)
Angola borders and has long-term links with Democratic Republic of Congo (DRC) as well as high levels of Human Immunodeficiency Virus (HIV) genetic diversity, indicating a potential role in the initial spread of the HIV-1 pandemic. Herein, we analyze 564 C2V3 and 354 pol publicly available sequences from DRC, Republic of Congo (RC) and Angola to better understand the initial spread of the virus in this region. Phylogeographic analyses were performed with the BEAST software. While our results pinpoint the origin of the pandemic to Kinshasa (DRC) around 1906, the introduction of HIV-1 to Angola could have occurred early between the 1910s and 1940s. Furthermore, most of the HIV-1 migrations out of Kinshasa were directed not only to Lubumbashi and Mbuji-Mayi (DRC), but also to Luanda and Brazzaville. Kinshasa census records corroborate these findings, indicating that the early exportation of the virus to Angola might be related to the high number of Angolans in Kinshasa at that time, originated mostly from the North of Angola. In summary, our results place Angola at the epicenter of the early HIV dissemination, together with DRC and RC. © 2016 Elsevier B.V.